Everyday magic : spells & rituals for modern living - Morrison, Dorothy, 1955- (Llewellyn Publications, 1998)
Are you tires of looking for ritual solutions for today's problems - computer viruses, traffic that drives you crazy, and stress that makes you forget your own name? Does the quest for obscure spell ingredients leave you exhausted and empty-handed? Now there's a better way to incorporate magic into your life without adding more stress to it!